2006
DOI: 10.1007/s10750-006-0099-y
|View full text |Cite
|
Sign up to set email alerts
|

Biological quality metrics: their variability and appropriate scale for assessing streams

Abstract: The concept of spatial scale is at the research frontier in ecology, and although focus has been placed on trying to determine the role of spatial scale in structuring communities, there still is a further need to standardize which organism groups are to be used at which scale and under which circumstances in environmental assessment. This paper contributes to the understanding of the variability at different spatial scales (reach, stream, river basin) of metrics characterizing communities of different biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 61 publications
0
16
1
1
Order By: Relevance
“…These effects are most strongly reflected by fish, benthic invertebrates and benthic diatoms (Hering et al, submitted). This contradicts to some degree with the results of Springe et al (2006), who found macrophytes and fish being more suitable for assessing ecological quality at the river basin scale, whereas metrics of macroinvertebrates and benthic diatoms were more appropriate at smaller scales.…”
Section: Type Of Anthropogenic Stresscontrasting
confidence: 70%
See 1 more Smart Citation
“…These effects are most strongly reflected by fish, benthic invertebrates and benthic diatoms (Hering et al, submitted). This contradicts to some degree with the results of Springe et al (2006), who found macrophytes and fish being more suitable for assessing ecological quality at the river basin scale, whereas metrics of macroinvertebrates and benthic diatoms were more appropriate at smaller scales.…”
Section: Type Of Anthropogenic Stresscontrasting
confidence: 70%
“…To tests these conjectures, comparative investigations on the response of different organism groups to stress are needed, which have, for example, been performed in the EU funded project STAR and are described in detail by Johnson et al (2006a, b), Springe et al (2006) and in addition by Hering et al (in press) and Johnson et al (in press). With this paper, we try to transform these results into a more general guidance, with focus on which organism group/groups can be used in biomonitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative physical, chemical as well as biological standards are needed against which streams/rivers in the region can be compared to determine the influence of cumulative stressor (Radwell & Kwak, 2005). Selection of reference sites was done based on evaluation of the biological, physical habitat and water quality data of streams as suggested by USEPA (2006) and Springe et al (2006). Similarly, Zhu & Chang (2008) also used cumulative data set based on physical, chemical and biological conditions of upper Yangtze River to define reference sites for calculation of biological integrity.…”
Section: Selection Of Reference Sitesmentioning
confidence: 99%
“…The EC Water Framework Directive (WFD; EC Parliament and Council, 2000) initiated a number of research focusing on basic concepts (Furse et al, 2006), typology of surface waters (Sandin & Verdonschot, 2006) and various kinds of methodical approaches (Comte et al, 2005;Besse-Lototskaya et al, 2006;Persson et at., 2006;Springe et al, 2006).…”
Section: Introductionmentioning
confidence: 99%